1988
DOI: 10.1073/pnas.85.12.4406
|View full text |Cite
|
Sign up to set email alerts
|

DNA base sequence changes and sequence specificity of bromodeoxyuridine-induced mutations in mammalian cells.

Abstract: By using a shuttle vector system developed in our laboratory, we have carried out studies on the molecular mechanism by which 5-bromodeoxyuridine (BrdUrd) induces mutations in mammalian cells. The target for mutagenesis in these studies was the Escherichia coli gpt gene that was contained within a retroviral shuttle vector and integrated into chromosomal DNA in mouse A9 cells. Shuttle vector-transformed cells expressing the gpt gene were mutagenized with BrdUrd and cells with mutations in the gpt gene were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Indeed, IdU has been previously shown to be less efficiently incorporated in DNA than BrdU and CldU (Franken et al, 1997). On the other hand, it has been reported that modulating the concentration of BrdU in the medium favours the occurrence of damages in the replicating DNA by an imbalancing in the ratio between the nucleotide pools leading to frequent BrdU/ guanine mispairing (Davidson et al, 1980(Davidson et al, , 1988. However, the addition of deoxycytidine, which prevents such an effect, even in excess over BrdU or CldU (Davidson et al, 1988), does not affect the association of replicating (halogenated) DNA with BCL6 bodies (unpublished data), suggesting therefore that this association is indeed correlated with the level of incorporation of the halogenated nucleotide into the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IdU has been previously shown to be less efficiently incorporated in DNA than BrdU and CldU (Franken et al, 1997). On the other hand, it has been reported that modulating the concentration of BrdU in the medium favours the occurrence of damages in the replicating DNA by an imbalancing in the ratio between the nucleotide pools leading to frequent BrdU/ guanine mispairing (Davidson et al, 1980(Davidson et al, , 1988. However, the addition of deoxycytidine, which prevents such an effect, even in excess over BrdU or CldU (Davidson et al, 1988), does not affect the association of replicating (halogenated) DNA with BCL6 bodies (unpublished data), suggesting therefore that this association is indeed correlated with the level of incorporation of the halogenated nucleotide into the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, dTTP, the nucleotide in excess, mispairs with guanine residues in replicating DNA molecules, resulting in GC3AT transitions (11,16,17,33). The misincorporation studies presented here are based upon previous work done in our laboratory dealing with the sequence-specific mode of dT mutagenesis in mammalian cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…The misincorporation studies presented here are based upon previous work done in our laboratory dealing with the sequence-specific mode of dT mutagenesis in mammalian cells (17). Those studies had shown that when cultured mouse cells carrying a single, chromosomally integrated copy of the bacterial gpt gene were subjected to high concentrations of dTTP, GC3AT transitions occurred preferentially at the 3Ј G residue of GG doublets in the gpt gene (11,33). The mutations that were observed in these experiments thus occurred under conditions of an imbalance in two specific nucleotide pools, namely, a high-dTTP pool and a low-dCTP pool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations